SIFAT FISIKOKIMIA DAN KANDUNGAN MIKRONUTRIEN PADA MADU KELULUT (Heterotrigona itama) DENGAN WARNA BERBEDA - Safinah S. Hakim; Siswadi; Reni S. Wahyuningtyas; Beny Rahmanto; Wawan Halwany; Fajar Lestari (BRIN Publishing, 2021)
Honey is one of the non-timber forest products, which has variety of benefits, among others health supplement andboosting stamina. One of the honey bee is kelulut (Heterotrigona itama). Consumers have certain preferences forkelulut honey based on colour appearance. This research was aimed to determine the colour of honey in relation with thequality of honey. Physicochemical and proximate analyses were carried out during this research. The results showed thatkelulut honey with dark color had higher reducing sugar content compared to light-colored honey. In addition, honey withdifferent colors has different micronutrients and benefits. The results of this study are expected to provide informationto consumers in making decisions when purchasing kelulut honey.